Faktor-Faktor yang Mempengaruhi Kunjungan Wisatawan ke Kota Sabang - Mawardi; Akhyar; Dedi Sufriadi (Jurnal EMT KITA, 2023)
The purpose of this study is to determine the impact of inflation and per capita income on domestic tourist visits to Sabang City and to determine the impact of exchange rates and annual tourism events on foreign tourist visits to Sabang City. The method used is a quantitative method using multiple linear regression. The data used are secondary data obtained from Sabang City BPS and Sabang City Tourism Office. Data analysis results show that per capita income has a positive impact on the number of domestic tourists in Sabang City, which is statistically significant. The inflation variable has a negative impact on the number of domestic tourists visiting Sabang City, but it is not statistically significant. And data analysis on the number of foreign tourists in Sabang City shows that the exchange rate has a negative impact on the number of foreign tourists in Sabang City, while the number of annual events has a positive impact. Statistically, exchange rate fluctuations are not significant, but the number of annual event fluctuations is statistically significant. Sabang City needs to make use of its superior potential in the region to become more professional and strengthen the economy of Sabang City.